Investment appraisal and evaluation: preserving tacit knowledge and competitive advantage. (1st January 2015) - Sims, Julian; Powell, Philip; Vidgen, Richard
This research asks if intuitive investment appraisal and evaluation are appropriate under conditions of rapid change, uncertain outcomes, limited information, and when competitive advantage derives from tacit knowledge. Measures and rational approaches to appraisal and evaluation require distal knowledge made explicit in documents and techniques. Converting valuable tacit knowledge, residing in individuals and organisational context, into coded distal knowledge, which is more easily replicated, risks jeopardising the uniqueness of competencies and capabilities that underpin competitive advantage. The research investigates e–learning projects in higher education and finds little evidence of formal rational investment appraisal and evaluation in IS projects characterised by uncertainty and a lack of clear information.